CYBERACTIVISM DAN SIMBOLISME GERAKAN EMPAT JARI PADA PEMILU 2024: ANALISIS PERAN MEDIA SOSIAL DALAM MOBILISASI MASSA - Abdul Malik Anwar Hamisi; Erlinda Wijayanti (Jurnal Komunikasi & Media Digital, 2024)
This study examines the phenomenon of cyberactivism through the four-finger movement in the 2024 Indonesian elections. In the 2024 elections, the four-finger symbol emerges as a significant form of political expression, signifying solidarity and resistance against certain candidates and depicting support for others. This research utilizes content analysis and social network analysis methods to reveal how this symbolism is used on social platforms and how it influences the formation of public opinion and election outcomes. The study evaluates the effectiveness of cyberactivism in Indonesian politics, highlighting the use of the four-finger symbol as a visual identification tool that strengthens solidarity and campaign coordination. The conclusions of this study indicate that social media and symbols like the four-finger movement play a critical role in facilitating political action, demonstrating the continuously adapting dynamics of politics to new technologies.